EDUKASI DAN SKRINING TERKAIT POSTUR TUBUH IDEAL SEBAGAI UPAYA PENCEGAHAN GANGGUAN POSTUR DINI BAGI PESERTA DIDIK SMP-IT AR-RAHMAH KOTA MAKASSAR (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Maintaining an ideal body posture plays a crucial role in daily life and long-term well-being. Habits related to technology use, work demands, and body positioning during activities can, often unconsciously, lead to posture-related issues. Poor posture can affect muscle function, causing discomfort such as pain, breathing difficulties, aesthetic concerns, and even abnormalities in spinal curvature. Posture-related problems are a significant concern, particularly among young individuals, and can increase the risk of developing other musculoskeletal disorders. Although musculoskeletal pain is believed to be influenced by multiple factors, the school environment is a key contributor, as children spend approximately 30% of their time at school, mostly in a seated position. During the learning process, students often sit with poor posture for extended periods. Additionally, carrying a relatively heavy school bag, especially when worn on only one side, can increase the risk of postural disorders such as scoliosis and forward head posture (FHP). Therefore, to mitigate the effects of improper body posture, early detection and education on the importance of maintaining good posture are essential. The objective of this initiative is to educate students on the significance of maintaining an ideal body posture and to facilitate early detection and prevention of postural disorders. Data collection was conducted by gathering primary data through body posture screening and assessing students’ general knowledge about posture. This was achieved through educational sessions, including direct presentations and hands-on demonstrations during the screening process.   ---   Menjaga agar postur tubuh tetap ideal memiliki peran krusial dalam kehidupan sehari-hari dan masa mendatang. Kebiasaan dalam menggunakan teknologi, tuntutan tanggung jawab, dan posisi tubuh saat beraktivitas tanpa disadari dapat menyebabkan gangguan pada postur. Postur tubuh yang buruk dapat mempengaruhi  kerja otot sehingga menimbulkan ketidaknyamanan seperti nyeri, gangguan pernapasan, estetika, bahkan masalah pada kurva tulang belakang. Masalah postur tubuh menjadi masalah yang cukup besar dan terdapat kecenderungan terjadi pada  kelompok usia muda dan dapat meningkatkan risiko terkena gangguan muskuloskeletal lainnya. Meskipun nyeri muskuloskeletal diyakini disebabkan oleh banyak faktor, namun lingkungan sekolah merupakan faktor penting, karena anak-anak menghabiskan sekitar 30% waktunya di sekolah terutama posisi duduk. Selama proses belajar di sekolah, siswa-siswi cenderung duduk dengan postur yang buruk dalam jangka waktu cukup lama. Selain itu, beban tas yang relatif berat terlebih lagi pemakaian tas hanya satu sisi dapat meningkatkan risiko terjadinya gangguan postur seperti skoliosis dan forward head posture (FHP). Maka dari itu, untuk mencegah efek dari postur yang tidak ideal,  dibutuhkan deteksi dan edukasi terkait pentingnya menjaga postur tubuh sejak dini. Tujuan dari kegiatan ini yaitu mengedukasi siswa terkait pentingnya menjaga postur tubuh yang ideal, dan deteksi dini/pencegahan terjadinya gangguan postur tubuh pada siswa.  Metode pengumpulan data dilakukan dengan pengambilan data primer melalui skrining postur tubuh dan pengetahuan umum mengenai postur diperoleh dengan cara edukasi melalui presentasi secara langsung dan peragaan langsung pada saat skrining berlangsung.
Keywords: Physiotherapy; posture; scoliosis; screening; students